Asuhan Kebidanan Pada Ibu Bersalin Normal Di Pmb Nurhayati Wilayah Kerja Puskesmas Air Tiristahun 2022 - Yunara, Yulia; Syahda, Syukrianti (Evidence Midwifery Journal, 2023)
Childbirth is a series of removal processes from the results of conception (fetus and placenta) with full-term gestational age and able to survive outside the womb through the birth canal or in other ways (Diana, 2019). Based on childbirth data obtained at PMB Nurhayati in 2019 there were 108 people.In 2020, the number of maternity mothers was 183 people, while the number of mothers who gave birth and were referred was 28 people with complications of KPD, Pre-eclampsia, placental retention, sunsang location and partus did not progress. In 2021, the number of normal maternity mothers was 155 people, while 30 people were referred with complications of KPD, placental retention, non-advanced partus, post term, gameli and sunsang location. The type of research used is descriptive research, which is a study conducted to descriptive or describe events that occur in the present which is carried out systematically with a case study design (Nursalam, 2013). The labor care carried out to Mrs. N went smoothly without complications and obstacles to childbirth. Labor lasts 2 hours. Childbirth starting from time I to time IV, the results of examination and monitoring have been attached to the partograph and documentation of obstetric care in the form of SOAP.